2017
DOI: 10.12693/aphyspola.131.1303
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Microstructure and Properties of Extruded Mg-Li-Al Alloys of α and α+ β Phase Composition using ECAP Processing

Abstract: Two magnesium based alloys containing 4.5 wt% Li and 1.5 wt% Al (alloy 1) and 9 wt% Li and 1.5 wt% Al (alloy 2) were cast under argon atmosphere and hot extruded at 350• C. Microstructure of alloy 1 consisted of hexagonal α phase of average grain size 20 µm and small aluminum rich precipitates being the most probably AlLi2Mg phase. Alloy 2 in the extruded form consisted of lamellas of α + β phases of thickness 5-20 µm and length above 100 µm. Significant grain refinement down to about 2 µm was observed in one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…EDS results of analysed intermetallic compounds revealed a high concentration of Al, Sr and Mg though Mg may come from the matrix. The observed intermetallic compounds have most probably resulted from the grain refinements addition in the form of Mg 17 Sr 2 , Mg 2 Sr or Al 4 Sr phase as suggested in [23][24][25], however, it must be noted that melting temperatures of proposed phases are 606°C, 680°C and 1040°C, respectively. Moreover, according to the Mg-Sr binary system [22] and suggestions in [23], the Mg 2 Sr phase is observed Mg alloys with a higher concentration of Sr (more than 1.5%).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…EDS results of analysed intermetallic compounds revealed a high concentration of Al, Sr and Mg though Mg may come from the matrix. The observed intermetallic compounds have most probably resulted from the grain refinements addition in the form of Mg 17 Sr 2 , Mg 2 Sr or Al 4 Sr phase as suggested in [23][24][25], however, it must be noted that melting temperatures of proposed phases are 606°C, 680°C and 1040°C, respectively. Moreover, according to the Mg-Sr binary system [22] and suggestions in [23], the Mg 2 Sr phase is observed Mg alloys with a higher concentration of Sr (more than 1.5%).…”
Section: Resultsmentioning
confidence: 90%
“…The addition of 0.2wt.% TiBor and 0.2wt.% AlSr10 master alloys cause decreases in nucleation temperature and solidus temperature to 579.32°C and 520°C, respectively. It was found that thermalderivative analysis of modified Mg-9Li-1.5Al alloys reveals an exothermic peak that probably becomes from nucleation of intermetallic compound as η(LiAl) phase [25]; however, more studies must be done. The addition of 0.2wt.% TiBor and 0.2wt.% AlSr10 master alloys decrease a crystallisation range and transition in solid state from 130°C to 105°C.…”
Section: Resultsmentioning
confidence: 99%
“…Darker particles have most probably resulted from the aluminium addition in the form of g(LiAl) phase as suggested in Fig. 2 Optical microstructure of as-cast and after modification of Mg-9Li-1.5Al alloy: a Mg-9Li-1.5Al, b Mg-9Li-1.5Al?0.2Zr, c Mg-9Li-1.5Al?0.2TiBor, d Mg-9Li-1.5Al?0.2Sr, e Mg-9Li-1.5Al?0.2TiBor?0.2Sr [8,9,19,20]. SEM analysis of marked circles shows high concentration of Al, indicating that it is g(LiAl) phase.…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of the initial annealed alloy (Fig. 2a) consists of wide major regions of equiaxed α phase (lighter) and minor amount of β phase distributed on the grain boundaries (darker) (Dutkiewicz et al, 2009). The microstructural percentage of these two phases has been determined to be almost 70% for α phase and 30% for β phase.…”
Section: Methodsmentioning
confidence: 99%